Therapeutic antibodies that target inflammatory cytokines in autoimmune diseases - Lai, Yuping (Int Immunol, 2016)
Inflammatory cytokines are key regulators of immune responses. Persistent and excessive production of inflammatory cytokines underscores the development of autoimmune diseases. Therefore, neutralizing inflammatory cytokines or antagonizing their receptor function is considered as a useful therapeutic strategy to treat autoimmune diseases. To achieve the success of such a strategy, understanding of the complex actions of these cytokines and cytokine networks is required. In this review we focus on four inflammatory cytokines—tumor necrosis factor α (TNFα), interleukin-6 (IL-6), IL-23 and IL-17—and dissect how the dysregulation of these cytokines regulates autoimmune diseases. On the basis of pre-clinical and clinical data, we specifically discuss the therapeutic rationale for targeting these cytokines and describe the potential adverse effects.